KEBIJAKAN KEPALA MADRASAH: STRATEGI MENINGKATKAN MUTU DI MADRASAH TSANAWIYAH SWASTA - Ridha Yanti; Tuti Indriyani; Fransisko Chaniago (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study focuses on the policies of the madrasah principal in improving educational quality at Madrasah Tsanawiyah Nurussa’adah, Teluk Rendah Ilir Village, Tebo Regency, Jambi Province. The objectives of this study are to examine the level of educational quality and to describe the policies implemented by the madrasah principal to enhance educational quality. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, while data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the educational quality at Madrasah Tsanawiyah Nurussa’adah has not yet reached an optimal level. This condition is reflected in learning processes that are not fully effective, limited use of learning methods and instructional media, and inadequate educational facilities and infrastructure. The policies implemented by the madrasah principal to improve educational quality include teacher professional development, improvement of educational facilities and infrastructure, strengthening collaboration with educational stakeholders, and more systematic management of financial resources. These policies aim to support more effective learning processes, enhance the quality of educational services, and achieve sustainable improvement in educational quality.